Applying STAR Strategy to Improve Studentsâ Vocabulary - VlasÃƒÂ¡kova, Jana; Manuhutu, Natalia (ELS Journal on Interdisciplinary Studies in Humanities, 2018)
The background of the study is the lack of adequate vocabulary by students due to lack of vocabulary exercises. The teacher teaches the students based on the textbook and running it to get the target of the curriculum which not paid attention to the students understanding when it caused them tended to be bored. This study was about the application of STAR strategy to improve studentsâ vocabulary. Thus, this study was aimed (1) to find out how STAR strategy application can improve studentsâ vocabulary (2) to explain the studentsâ perception about learning vocabulary through STAR strategy. The design of this study was a pre-experimental method. The subject of this study was first grade students of the senior high school. Furthermore, the data were gained through a test (pre-test and post-test) and non-test (questionnaire). The test was used to know studentsâ competence before and after the implementation, while a questionnaire was used to know studentsâ perceptions towards STAR strategy. The significant findings of the recent study were the studentsâ vocabulary mastery is significantly increased. It can be seen from the result of studentsâ average score and good responses by students. Studentsâ average score from pre-test was 22 and the post-test was 73. The t-test score was higher than the t-table (2,09< 13,66 > 2, 86). It was meant that researchersâ hypothesis could be accepted. Finally, the STAR strategy could be implemented practically and pedagogically in improving studentsâ vocabulary.